Soy Meera Malik - Borregon, Marcos (Spain : Lapierna Audiovisual, 2008)
A film about Meera, an ambitious young girl living with her family in one of the slums of Calcutta. Her daily routine starts at 5 in the morning when she cooks breakfast for the whole family, followed by school and further household chores. With all the poverty, garbage and disillusionment around, Meera is one of the lucky girls who gets to go to school and thus can weave her dreams of one day rising above her past.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films